A Pharmacokinetic Dose-Optimization Study of Cabotegravir and Bictegravir in a Mouse Pregnancy Model - Haneesha Mohan; Kieran Atkinson; Birgit Watson; Chanson J. Brumme; Lena Serghides (Pharmaceutics, 2022)
Animal pregnancy models can be useful tools to study HIV antiretroviral safety and toxicity and to perform mechanistic studies that are not easily performed in humans. Utilization of clinically relevant dosing in these models improves the relevance of the findings. Cabotegravir and bictegravir are new integrase strand transfer inhibitors (INSTIs), recently approved for the treatment of people living with HIV. Studies of these drugs in pregnancy are very limited. The objective of this study was to perform a dose-optimization study of cabotegravir and bictegravir in a mouse pregnancy model with the goal of determining the dose that would yield plasma drug concentrations similar those observed in humans. Pregnant mice were administered increasing doses of cabotegravir or bictegravir in combination with emtricitabine and tenofovir by oral gavage from gestational day 11.5 to 15.5. Drug concentrations in the maternal plasma at 1 h and 24 h post drug administration and in the amniotic fluid at 1 h post drug administration were determined using high-performance liquid chromatography coupled with tandem mass spectrometry. A review of cabotegravir and bictegravir human pharmacokinetic studies are also reported. We hope these data will encourage studies of HIV antiretroviral safety/toxicity and mechanistic studies in animal pregnancy models.